Strategies for Dodging the Obstacles in CAR T Cell Therapy - Safarzadeh Kozani, Pooria; Safarzadeh Kozani, Pouya; Rahbarizadeh, Fatemeh; Khoshtinat Nikkhoi, Shahryar (Frontiers in Oncology, 2021)
Chimeric antigen receptor (CAR) T cell therapy has offered cancer patients a new alternative therapeutic choice in recent years. This novel type of therapy holds tremendous promise for the treatment of various hematologic malignancies including B-cell acute lymphoblastic leukemia (B-ALL) and lymphoma. However, CAR T cell therapy has experienced its ups and downs in terms of toxicities and efficacy shortcomings. Adverse events such as cytokine release syndrome (CRS), neurotoxicity, graft rejection, on-target off-tumor toxicities, and tumor relapse have tied the rescuing hands of CAR T cell therapies. Moreover, in the case of solid tumor treatment, CAR T cell therapies have not yielded encouraging results mainly due to challenges such as the formidable network of the tumor microenvironments (TME) that operates in a suppressive fashion resulting in CAR T cell dysfunction. In this review, we tend to shine a light on emerging strategies and solutions for addressing the mentioned barriers. These solutions might dramatically help shorten the gap between a successful clinical outcome and the hope for it.